THE CONCEPT AND TERMINOLOGY OF IKHLAS IN AL-QUR’AN AND ITS APPLICATION - Achmad Ramadhan (UIN Sumatera Utara, 2021)
This paper is aimed to describe the most important concept in doing, namely إخلاص and its application. The description of this important concept covers some aspects: 1) the definition and meaning of إخلاص both etymologically and terminologically, 2) the interpretations of the Muslim scholars dealing with the concept, 3) the conjugation or تَصْرِيْفٌ of the term إخلاص, 4) the definition and meaning of إخلاص, 5) the instruction to apply إخلاص in the religious observance, 6) the advantage of إخلاص in al-Qur’an. Based on the descriptions above, it can be concluded that the concept of إخلاص covers some aspects as follows: 1) the term إخلاص is not directly written as an order for instance, but it’s derivations or the other verb, 2) the term إخلاص deals with tauhid purity and all kinds of religious service either العبادة المحضة or العبادة غير المحضة , 3) The term of إخلاص with its derivations in al-Qur’an goes not only to the verbs, like the muslim servant’s activities, like لِيَعْبُدُوا اللَّهَ مُخْلِصِينَ , but also to the nouns, likeخالصا لبنا (QS. النحل : 66), 4) the application of إخلاص starts from a heart decision, 5) to have and apply إخلاص is a key to have the immense value, Heaven.